(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The presence of Leyptocybe invasa was noted on seedlings of Eucalyptuscamaldulensis, showing galls, in the nursery of the National Forestry Corporation atSoba, Khartoum State, Sudan. Galling caused twisting of leaves and stunting ofseedlings growth. About 100 000 seedlings were infested, and the percentage ofinfestation ranged between 85% and 100% on 1.5- 7.0 month-old seedlings. This is thefirst record of L. invasa in Sudan